2014
DOI: 10.1117/1.oe.53.3.031211
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive testing potential evaluation of a terahertz frequency-modulated continuous-wave imager for composite materials inspection

Abstract: The sub-terahertz (THz) frequency band has proved to be a noteworthy option for nondestructive testing (NDT) of nonmetal aeronautics materials. Composite structures or laminates can be inspected for foreign objects (water or debris), delaminations, debonds, etc., using sub-THz sensors during the manufacturing process or maintenance. Given the harmless radiation to the human body of this frequency band, no special security measures are needed for operation. Moreover, the frequency-modulated continuous-wave sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 14 publications
1
40
0
Order By: Relevance
“…This downgraded the best possible depth resolution by roughly a factor of 2. The overall results of the initial test measurements are in excellent accordance to the outcomes of [1]. On the other hand, the penetration depth in terahertz measurements is, in general, larger at lower frequencies.…”
Section: Preliminary Investigationssupporting
confidence: 75%
See 3 more Smart Citations
“…This downgraded the best possible depth resolution by roughly a factor of 2. The overall results of the initial test measurements are in excellent accordance to the outcomes of [1]. On the other hand, the penetration depth in terahertz measurements is, in general, larger at lower frequencies.…”
Section: Preliminary Investigationssupporting
confidence: 75%
“…The latter also provides a higher modulation For the initial study, terahertz images of test samples were acquired by raster-scanning the samples in reflection geometry with three different frequency-modulated continuous-wave (FMCW) transceiver units operating at 100 GHz, 150 GHz, and 300 GHz, while providing modulation bandwidths of around 40 GHz, 60 GHz, and 90 GHz, respectively. For the measurements on the test panels, we employed the same quasi-optical system, as described in [1]. Figure 2 shows two exemplary terahertz imaging results at roughly the same depth position around the center in one of the samples.…”
Section: Preliminary Investigationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14] Many studies have been reported regarding NDE for CFRP by using THz technologies. Redo-Sanchez and Karpowicz 15 and Karpowicz and Dawes 16 applied THz continuous and pulsed wave technology in reflection mode to detect burn damage of CFRP.…”
Section: Introductionmentioning
confidence: 99%